ifo World Economic Survey August 2018 - Dorine Boumans (ifo World Economic Survey, 2018)
World Economic Climate: ifo World Economic Climate Deteriorates Further - Advanced Economies: Optimism in Advanced Economies Fades - Emerging and Developing Economies: Economic Climate Indicator for Emerging Market and Developing Economies Plunges - Special Topic: How Resilient are the World's Economies to a New Financial Crisis?
Keywords: 330